Gliomatosis peritonei in mature ovarian teratoma - Reyna-Villasmil, Eduardo (2020)
Ovarian teratomas are tumors derived from the three germinal layers. Gliomatosis peritonei is a rare condition characterized by glial tissue implants in peritoneum, commonly associated with immature ovarian teratoma, but not with mature teratomas. Definitive diagnosis is based on histopathological examination. Currently, there are no guidelines for its follow-up. Prognosis is favorable; however, implants may present fibrotic regression or exceptionally degenerate into glioblastoma. Treatment should be similar to that of metastatic ovarian carcinoma if immature glial tissue or other teratomatous components are found in peritoneum or omentum. Long-term follow-up is necessary in patients with residual peritoneal disease due to risk of recurrence and malignant transformation. We present a case of gliomatosis peritonei associated to mature ovarian teratoma.